Screening, assessment and diagnosis in the eating disorders: findings from a rapid review - Emma Bryant; Karen Spielman; Anvi Le; Peta Marks; National Eating Disorder Research Consortium; Stephen Touyz; Sarah Maguire (Journal of Eating Disorders, 2022)
Abstract Background Limited screening practices, minimal eating disorder training in the healthcare professions, and barriers related to help-seeking contribute to persistent low rates of eating disorder detection, significant unmet treatment need, and appreciable associated disease burden. The current review sought to broadly summarise the literature and identify gaps relating to the screening, assessment, and diagnosis of eating disorders within Western healthcare systems. Methods This paper forms part of a Rapid Review series scoping the evidence base for the field of eating disorders, conducted to inform the Australian National Eating Disorders Research and Translation Strategy 2021–2031, funded and released by the Australian Government. ScienceDirect, PubMed and Ovid/Medline were searched for studies published between 2009 and mid 2021 in English. High-level evidence such as meta-analyses, large population studies and Randomised Control Trials were prioritised through purposive sampling. Data from selected studies relating to Screening, Assessment and Diagnosis of eating disorders were synthesised and are disseminated in the current review. Results Eighty seven studies were identified, 38% relating to screening and 62% to assessment and diagnosis. The majority of screening studies were conducted in university student samples, showing high prevalence but only modest improvements in help-seeking in those studies that followed up post-screen. In healthcare settings, clinicians continue to have difficulty identifying eating disorder presentations, particularly Binge Eating Disorder, Other Specified Feeding or Eating Disorders, and sub-threshold eating disorders. This is preceded by inadequate and frequently homogenous screening mechanisms and exacerbated by considerable personal and health-system barriers, including self-stigma and lack of resourcing. While all groups are at risk of delayed or no diagnosis, those at particular risk include LGBTQ+ and gender diverse individuals, individuals living in larger bodies, and males. Conclusions A majority of individuals with eating disorders remain undiagnosed and untreated despite a high prevalence of these conditions and increased advocacy in recent years. Research into improving detection and clinician diagnostic skill is extremely limited. Innovative empirical research is strongly recommended to address significant individual and health-system barriers currently preventing appropriate and timely intervention for many. Plain English Summary Limited screening in healthcare settings and low rates of eating disorder training in the healthcare professions are just some of the barriers to help-seeking which may contribute to delayed intervention and diagnosis in the eating disorders. This has significant impacts, prolonging treatment when it is finally received, and increasing healthcare costs for both the individual and the healthcare system. The current review is part of a larger Rapid Review series conducted to inform the development of Australia’s National Eating Disorders Research and Translation Strategy 2021–2031. A Rapid Review is designed to comprehensively summarise a body of literature in a short timeframe, often to guide policy-making and address urgent health concerns. The Rapid Review synthesises the current evidence-base and identifies gaps in eating disorder research and care, in order to guide decision making and address urgent health concerns. This paper gives a critical overview of the scientific literature relating to the current state of screening, assessment, and diagnosis of eating disorders within Western healthcare systems that may inform health policy and research in an Australian context. It covers screening initiatives in both general and high-risk populations; personal, clinician and healthcare system challenges relating to help-seeking; and obstacles to accurate and timely clinical diagnosis across the eating disorders.